The influence of instructional leadership on professional learning communities practices - Zuhailla Za’aba,; Bity Salwana Alias, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Instructional leadership plays a particular role in school since its role has always been to impact effective teaching and learning processes. Instructional leadership practices is essential in promoting professional development among teachers. Professional learning communities (PLCs) are recognized as one of effective organization practice involving collaborative learning to improve school performance. This paper emphasize the importance of promoting collaborative learning among teachers by instructional school leaders. Therefore, this conceptual paper aims to discuss the influence of instructional leadership practices among school leaders towards PLCs practices. Hence, issues and challenges in implementing PLCs in schools are discussed. As a result, this conceptual paper offers insights with implications for policy, practice, and training. The policy makers should emphasize the encouragement of PLCs implementation to promotes its beneficial practice for school performance. Besides, school leaders should focus on instructional leadership strategies that highlight best practices to promote collaborative learning opportunities for professional development among teachers. This paper also underscores the significance of equipping school leaders with the necessary skills to foster a positive school climate, thereby enhancing the successful implementation of Professional Learning Communities (PLCs) among teachers. In conclusion, instructional leadership plays an important role in supporting the PLCs implementation in school.